Pengaruh Suplementasi Ampas Tahu, Ampas Tempe dan Ampas Kecap dalam Ransum Terhadap Performan Domba Lokal Jantan - Handayanta, Eka (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2007)
The aim of this research to determine the effect of supplementation of tofu. tempe, and soy sauce waste in ration on male local sheep performance. This research was carried out during three month, take place on July until October 200E in Minifarm Dept. of Animal Science, Agriculture Faculty of Sebelas Maret University, located in Jatikuwung. Gondangrejo, Karanganyar. It used 12 male local sheeps with average body weight of 15.86 ±0.93 kg, divided into four treatments and three replications, each replication consist of one sheep. The ration consisted of king grass only as basal diet, as many as four percent base on body weight. The treatment given is in the form of feed supplement, that namely without supplement (RO), 250 gram tofu waste (R1), 250 gram tempe waste (R2), and 250 gram soy sauce waste (R3). The data variables collected were feed consumption, dry and organic matter digestibility, crude protein consumption, energy consumption, average daily gain, and feed conversion ratio. All of data except average daily gain was analyzed by completely randomized design one way classification. While average daily gain was analyzed by covariance analyze. The result were significant followed by Duncan new multiple range test. The result showed that average of R0, RI, R2 and R3 for feed consumption 430.52; 720.44; 704.44; 549.08 gram/day, dry matter digestibility (%) 61,07; 72,46; 69,68: 63,60, organic matter digestibility (%) 64,41: 74,94; 72.41; 64,7 1, crude protein consumption 47.66; 106.77; 85.83; 73.70 gram/day, energy consumption 281.82; 482.65; 432.67; 330.83 gram/day, average daily gain 50.00.1X00: 116.19; 38.10 gram/day and feed conversion ratio 8.74; 5.61; 6.06; 15.2. The result of variance analyze showed that feed supplementation have highly significant effect (P<0.01) on all of the data variable colected. Conclusion of this research was supplementation of tofu waste and tempe waste could improved performance, while soy sauce waste could not improved the performance of male local sheep. Key words : sheep, tofu waste, tempe waste, soy sauce waste, performance